Irradiation-resistance conferred by superoxide dismutase: possible adaptive role of a natural polymorphism in Drosophila melanogaster. - Peng, T X (1986)
The toxic effects of ionizing radiation to DNA are thought to be due to the generation of the superoxide radical, 02-. Superoxide dismutase (SOD), which scavenges 02-., has been invoked as a protecting enzyme against ionizing radiation in viruses, bacteria, mammalian cells in culture, and live mice. We now demonstrate that SOD is involved in the resistance of Drosophila melanogaster against irradiation. The protection is greatest when flies carry the S form of the enzyme (which exhibits highest in vitro specific activity), intermediate when they carry the F form of the enzyme, and lowest when they are homozygous for N, an allele that reduces the amount of the enzyme to 3.5% of the normal level. Natural selection experiments show that the fitness of the high-activity S allele is increased in an irradiated population relative to the nonirradiated control. These results point towards a possible adaptive function of the S/F polymorphism found in natural populations of D. melanogaster.